Stray dog [videorecording (DVD)] (Criterion collection, 2004)
A bad day gets worse for rookie detective Murakami when a pickpocket steals his gun on a hot, crowded bus. Desperate to right the wrong, he goes undercover, scavenging Tokyo's sweltering streets for the thief, whose desperation has led him to a life of crime. With each step, the cop and the criminal's lives become more intertwined and the investigation becomes an examination of Murakami's own dark side --